IEEE-EMBS International Conference on Biomedical and Health Informatics (BHI) 2014
DOI: 10.1109/bhi.2014.6864466
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo simulation of diabetic macular edema changes on optical coherence tomography data

Abstract: Optical coherence tomography (OCT) scans were acquired from healthy controls and patients with diabetic macular edema (DME), a common complication of diabetes characterized by increased retinal thickness due to fluid accumulation. The collected OCT data was divided into three distinct groups: healthy subjects, DME patients with significantly increased outer nuclear layer (ONL) thickness and DME patients without visible changes in the ONL. For each group, the ONL was segmented and processed, yielding a represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…However, SD-OCT findings revealed 42.1% of these cases have no ME. Hence, SD-OCT findings can be used as adjunct tool for DME screening Magdy et al [69] 13 ✓ Â Â OCT thickness map is correlated with FA leakage pattern and reported a highest correlation coefficient of 0.9086 Querques et al [63] 63 Â ✓ ✓ CMT is increased for NCSME ð294:5 7 23:5 μmÞ and CSME ð385:6 7 75:1 μmÞ compared with normal ð272:57 16:2 μmÞ subjects Regatieri et al [61] 49 Â Â ✓ SD-OCT findings show that subfoveal choroidal thickness is thinner ð63:3 μmÞ for DME patients Roychowdhury et al [70] 120 Â Â ✓ Cyst in DME class is segmented automatically using OCT images and reported a correlation rate of 90% Correia et al [66] 24 Â Â ✓ Increased ONL thickness is observed between normal and DME classes Dmuchowska et al [56] 51 ✓ ✓ ✓ There is no significant correlation between foveal avascular zone size and RT measured using OCT. Hence, OCT cannot replace the FA for ischemic DME…”
Section: Diagnostic Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, SD-OCT findings revealed 42.1% of these cases have no ME. Hence, SD-OCT findings can be used as adjunct tool for DME screening Magdy et al [69] 13 ✓ Â Â OCT thickness map is correlated with FA leakage pattern and reported a highest correlation coefficient of 0.9086 Querques et al [63] 63 Â ✓ ✓ CMT is increased for NCSME ð294:5 7 23:5 μmÞ and CSME ð385:6 7 75:1 μmÞ compared with normal ð272:57 16:2 μmÞ subjects Regatieri et al [61] 49 Â Â ✓ SD-OCT findings show that subfoveal choroidal thickness is thinner ð63:3 μmÞ for DME patients Roychowdhury et al [70] 120 Â Â ✓ Cyst in DME class is segmented automatically using OCT images and reported a correlation rate of 90% Correia et al [66] 24 Â Â ✓ Increased ONL thickness is observed between normal and DME classes Dmuchowska et al [56] 51 ✓ ✓ ✓ There is no significant correlation between foveal avascular zone size and RT measured using OCT. Hence, OCT cannot replace the FA for ischemic DME…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Features are extracted using logarithmic space, linear space and exponential distribution from the OCT images and SVM classifier and reported an accuracy of 84.2%. Correia et al [66] used HD-OCT to analyse normal, Outer Nuclear Layer (ONL) thickness changes in patients with DME. Initially, manual segmentation of ONL is performed.…”
Section: Mrk Mookiah Et Al / Computers In Biology and Medicine ∎ mentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies are conducted to analyze the retinal blood vessels and layers to help ophthalmologists diagnose different retinal diseases. Most of these studies are based on analyzing the colored fundus images, 1,7,8,9,10,11,12,13,14 optical coherence tomography (OCT) scans, 15,16,17,18,19 and OCTA scans. 20,21,22 In the remaining part of this section, we discuss the CAD systems based on these three imaging modalities.…”
Section: Introductionmentioning
confidence: 99%
“…They also localized cysts for DME patients. Correia et al 17 detected the variations that occurred in the outer nuclear layer (ONL) in DME cases. A Monte Carlo algorithm with a model for the ONL is utilized to simulate an A-scan for two groups of healthy and diseased subjects to detect the changes.…”
Section: Introductionmentioning
confidence: 99%